PENGARUH PERLAKUAN PENDAHUULAN TERHADAP KECEPATAN PENGERINGAN KAYU MANGIUM - Krisdianto Krisdianto; Jamaludin Malik (Pusat Penelitian dan Pengembangan Hasil Hutan, 2004)
One of the problems faced in mangium (Acacia mangium Willd.) wood utilization is its low drying rate. Some pre-treatment methods: steaming, boiling and microwave heating have been examined to improve its drying time. After treated with steaming, boiling and microwave heating, six various dimension of mangium samples were dried in oven. During drying process, the samples were weighed two hoursly in the first 24 hours to determine the pattern of moisture reduction. Microwave heating and boiling enhance its drying time in all sample sizes, while steaming was only effective for samples with thickness below 5 cm. Boiling leads to generate drying defects such as wrapping, twist, bow, and surface checks, while microwave heating and steaming methods caused minor drying defects.